Mikalojaus Daukšos Postilės slavizmų morfologinė integracija - Voitkevič, Božena (Baltistica, 2010)
MORPHOLOGICAL INTEGRATION OF SLAVISMS IN Postilla BY MIKALOJUS DAUKŠAThis paper deals with the morphological integration of Slavisms into the Lithuanian language. An attempt was made to determine in what cases and due to what reasons Slavic loanwords integrated into a certain type of declension system. It also discusses the problem of gender nonconformity (Slavic languages have three genders: masculine, feminine and neuter, while the Lithuanian language has two). For example, the research of Slavisms in Daukša’s Postilla indicated that if in Slavic languages the stem was soft then a Slavism would not integrate into o, a, u stems in the Lithuanian language. The present research shows that it is important to pay attention not to the added and rejected endings (cf. Valeckienė 1967; Laučiūtė 2007), but to concurrence or non-concurrence of declension types.
Keywords: slavizmai; skolinių morfologinė integracija; Daukša; Postilė; senieji raštai